Perbedaan kompres hangat jahe dan back massage terhadap penurunan skala nyeri ekstrimitas bawah pada lansia dengan rheumatoid athritis - Pujastuti, Ni Kadek Dwi Mas; Mertha, I Made; Dewi, I Dewa Ayu Ari Rama (Coping: Community of Publishing in Nursing, 2019)
Rheumatoid arthritis is a musculoskeletal disease often  attack the small joints in elderly and causes lower  extremities pain. The complementary medicine that can reduce the pain scale of rheumatoid arthritis is warm ginger compress and back massage. The aim of this study was to determine the difference of warm ginger compress and back massage to reduce the lower extremities pain in elderly with rheumatoid. This was a quasi-experimental design study (two-group pre-post). There were 30 samples devided into two groups, warm ginger compress and back massage. Data was collected with NRS which consist  0-10. Both of this therapy  are given every two days for two weeks with 10 minutes for duration. The result of Wilcoxon Rank Test for within group warm ginger compress and back massage indicated that there was influence warm ginger compress and back massage to reduce the lower extremities pain, which is showed by p= 0,000 on warm ginger compress group and p= 0,001 on back massage group. The result of Mann Whitney test indicated that there was differences between warm ginger compress and back massage to reduce the lower extremities pain scale which is showed by p= 0,017. Most respondents says that warm ginger compress is more effective than back massage showed by the cost, time and experience during intervention. Based on this study, it is recommended to apply warm ginger compress to reduce the lower extremities pain scale in elderly with rheumatoid arthritis.
Keywords: Back Massage, Lower Extrimities Pain, Rheumatoid Athritis, Warm Ginger Compress